2012
DOI: 10.1590/s1516-35982012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de cereais de inverno de duplo propósito na depressão central do Rio Grande do Sul

Abstract: RESUMO -Esta pesquisa foi conduzida com o objetivo de avaliar a precocidade, a produtividade e as características do dossel de 12 genótipos de seis espécies de cereais de inverno de duplo propósito (forragem e grãos) submetidos ao corte na região da Depressão Central do Rio Grande do Sul. As espécies e os genótipos testados foram: trigo BRS 277, BRS Guatambu, BRS IntroduçãoNo Sul do Brasil, uma das maiores limitações da atividade pecuária é a carência de forragem no período entre o outono e início do inverno,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
2
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 8 publications
4
38
2
12
Order By: Relevance
“…Other authors found a similar result to this work. According to the results of Meinerz et al (2012), wheat BRS Tarumã showed higher forage production in the second cut compared to the first one. Quatrin et al (2017), evaluating the nutritional value of dual-purpose wheat BRS Tarumã in 3 grazing cycles, observed higher forage yield in the last grazing cycle (2,070 kg ha -1 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Other authors found a similar result to this work. According to the results of Meinerz et al (2012), wheat BRS Tarumã showed higher forage production in the second cut compared to the first one. Quatrin et al (2017), evaluating the nutritional value of dual-purpose wheat BRS Tarumã in 3 grazing cycles, observed higher forage yield in the last grazing cycle (2,070 kg ha -1 ).…”
Section: Resultsmentioning
confidence: 97%
“…According to Meinerz et al (2012), BRS Tarumã presents a balance between forage and grain yield, and is indicated for dual-purpose management. The correct management of sowing density, nitrogen fertilization and number of cuts does not affect grain yield and may allow the use of dual-purpose wheat BRS Tarumã in crop-livestock integration systems in the southern region of Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Mariani et al (2012), de 1178kg/ha, ao trabalharem com trigo BRS Tarumã, submetido a dois pastejos. Entretanto, Meinerz et al (2012), na mesma região, após três cortes, obtiveram produtividades de 2767 e 3468kg/ha para BRS Tarumã e Umbu, respectivamente. Os valores obtidos para o rendimento são considerados baixos e devem-se, especialmente, às condições meteorológicas, com valores de precipitação pluviométrica e de temperatura superiores às normais climatológicas para os meses de setembro e outubro (Fig.…”
Section: Resultsunclassified
“…Dentre esses materiais, o cultivar BRS Tarumã se destaca pelo intenso afilhamento e pela maior resistência às doenças (Fontaneli, 2007), enquanto o BRS Umbu destaca-se pelo ciclo mais precoce e pela maior produção de grãos (Meinerz et al, 2012). No entanto, há poucos estudos que avaliam esses cultivares em condições de pastejo com vacas em lactação, além de eles terem sido conduzidos em regiões específicas.…”
Section: Introductionunclassified
“…In certain periods, i.e., the dry season, the food supply by pastures is insufficient to meet the animals' needs, which could be circumvented by supplementing grains in high-cost diets, hay or silage (Meinerz et al 2012).…”
Section: Introductionmentioning
confidence: 99%